A novel discovery of a long terminal repeat retrotransposon-induced hybrid weakness in rice. (20th December 2018) - Nadir, Sadia; Li, Wei; Zhu, Qian; Khan, Sehroon; Zhang, Xiao-Ling; Zhang, Hui; Wei, Zhen-Fei; Li, Meng-Ting; Zhou, Li; Li, Cheng-Yun; Chen, Li-Juan; Lee, Dong-Sun
Abstract : Gene activation caused by long terminal repeat retrotransposon insertion in the promoter of a newly discovered gene, Hwc3, leads to hybrid weakness in intrasubspecific japonica rice hybrids. Abstract: Hybrid weakness is a post-zygotic hybridization barrier frequently observed in plants, including rice. In this study, we describe the genomic variation among three temperate japonica rice ( Oryza sativa ssp. japonica ) varieties 'Aranghyangchalbyeo' ('CH7'), ' Sanghaehyangheolua' ('CH8') and ' Shinseonchalbyeo' ('CH9'), carrying different hybrid weakness genes. The reciprocal progeny obtained from crossing any two varieties displayed characteristic hybrid weakness traits. We mapped and cloned a new locus, Hwc3 (hybrid weakness 3), on chromosome 4. Sequence analysis identified that a long terminal repeat (LTR) retrotransposon was inserted into the promoter region of the Hwc3 gene in 'CH7'. A 4-kb DNA fragment from 'CH7' containing the Hwc3 gene with the inserted LTR retrotransposon was able to induce hybrid weakness in hybrids with 'CH8' plants carrying the Hwc1 gene by genetic complementation. We investigated the differential gene expression profile of F1 plants exhibiting hybrid weakness and detected that the genes associated with energy metabolism were significantly down-regulated compared with the parents. Based on our results, we propose that LTR retrotransposons could be a potential cause of hybrid weakness in intrasubspecific hybrids in japonica rice. Understanding the molecular mechanisms underlying intrasubspecific hybrid weakness is important for increasing our knowledge on reproductive isolation and could have significant implications for rice improvement and hybrid breeding.